Rehabilitation of shortened dental arches: A fifteen‐year randomised trial. (21st March 2021) - Walter, Michael Horst; Marré, Birgit; Dreyhaupt, Jens; Heydecke, Guido; Rauch, Angelika; Mundt, Torsten; Hannak, Wolfgang; Kohal, Ralf Joachim; Kern, Matthias; Nothdurft, Frank; Hartmann, Sinsa; Böning, Klaus; et al.
Abstract: Background: Few long‐term studies on treatments in the shortened dental arch (SDA) are available. Objective: The objective of this trial was to analyse the long‐term success of two different treatment concepts. Methods: Patients over 35 years of age with missing molars in one jaw and at least the canine and one premolar present on both sides were eligible. In the partial removable dental prosthesis (PRDP) group (N = 81), molars and missing second premolars were replaced by a precision attachment retained prosthesis. In the SDA group (N = 71), the dental arch ended with the second premolar that had to be present or replaced by a cantilever fixed dental prosthesis. Follow‐up examinations were carried out over 15 years. Results: A comprehensive outcome variable comprised four failure categories for which Kaplan‐Meier survival (success) analyses were conducted. Half of the patients exhibited a continuous preservation of the per protocol prosthetic status that remained totally unaffected by complications for more than 10 years. The event‐free success rates for moderate or worse failure implied a loss of the per protocol prosthetic status. The respective survival rates fell below 50% at 14.2 years in the PRDP group and 14.3 years in the SDA group. In none of the analyses, a significant group difference was found. Conclusions: In patients with an SDA condition, changes in the prosthetic status have to be expected. The affected proportion increases almost linearly from shortly after treatment and comprises the majority after 15 years. The influence of the examined treatments on success appears to be low.